Description of a new species of the leafhopper genus Mimotettix Matsumura (Hemiptera: Cicadellidae: Deltocephalinae) from China - Hu, Shangmi; Ran, Siyu; Xing, Jichun (Zootaxa, 2025)
A new leafhopper species: Mimotettix fodingshanensis sp. nov. is described and illustrated from Guizhou Province, China. A checklist and a key to species of the genus from China are provided. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).